Generalized effective-potential Landau theory for the two-dimensional extended Bose-Hubbard model - Lin, Zhi; Yang, Ming (Physics letters. A, 2019)
We analytically study the quantum phase diagrams of ultracold dipolar Bose gases in an optical square lattice at zero temperature by using the generalized effective-potential Landau theory (GEPLT). For a weak nearest-neighbor repulsion, our analytical results are better than the third-order strong-coupling expansion theory calculation. In contrast to a previous quantum Monte Carlo (QMC) simulation, we analytically calculate phase transition boundaries up to the third-order hopping, which are in excellent agreement with QMC simulations for second-order phase transition. •In contrast to strong-coupling expansion theory (a non-universal theory), we introduce a universal theory—the GEPLT.•The strong-coupling theory is invalid (valid) for obtaining CDW (MI) lobes but the GEPLT is valid for obtaining both lobes.•The GEPLT is better than the third-order strong-coupling perturbation theory for obtaining the tips of the MI lobes.•At ZV=1.5U, the CDW lobes for the second-order phase transition part given by our method coincide with the QMC simulations.